2008
DOI: 10.1136/sti.2008.029827
|View full text |Cite
|
Sign up to set email alerts
|

Men who pay for sex in Spain and condom use: prevalence and correlates in a representative sample of the general population

Abstract: The prevalence of paying for heterosexual sex among Spanish men is the highest ever described in developed countries. The many variables associated with paying for sex and condom use permit the characterisation of male clients of prostitution and should facilitate targeting HIV prevention policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
2
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 27 publications
4
31
2
4
Order By: Relevance
“…As with other studies, being older and having a lower level of education seems to be a characteristic found among men who pay for sexual services (Pitts et al 2004;Belza et al 2008;Buttmann et al 2011), but this study also adds differences with respect to employment status and level of income (Jewkes et al 2012b). …”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…As with other studies, being older and having a lower level of education seems to be a characteristic found among men who pay for sexual services (Pitts et al 2004;Belza et al 2008;Buttmann et al 2011), but this study also adds differences with respect to employment status and level of income (Jewkes et al 2012b). …”
Section: Discussionmentioning
confidence: 70%
“…This survey was published by the Ministry of Health and the National Statistics Institute in 2003, (INE 2004) and showed that in men aged 18 to 49 years old, 25.4% had paid for sexual services at some time, and 5.7% had done so in the previous 12 months. This behaviour was more prevalent in older men, those who had not been married or were not living with a partner, had low levels of education, were not born in Spain, were members of a religious group, had started their economic https://doi.org/10.3989/ris.2018.76.2.17.47 activity at a very early age and those who had been drunk in the previous 30 days (Belza et al 2008). Other studies have shown different figures in Spain for the previous year: 9.9% (Hubert et al 1998) and 11% of men (Carael et al 2006), with Spain being in both cases one of the countries with the highest rates of men paying for sexual services.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, studies of sexual risk behavior in male clients of female sex providers worldwide have received considerable attention (Belza et al, 2008;Goldenberg et al, 2010;Gomes do Espirito Santo & Etheridge, 2005;Hong, 2008;Jones et al, 2015;Schei & Stigum, 2010;Yang, Attané, & Li, 2014). Conversely, available research on condom use and sexual risk in male clients of independently operating indoor sex providers in the United States was minimal, largely due to the difficulty in accessing this particular client population.…”
Section: Articlementioning
confidence: 99%
“…Although recent research on condom use in clients of sex providers has included adult men of all ages in a variety of settings (e.g., Belza et al, 2008;Hong, 2008;Yang et al, 2014), the present study focuses on hobbyists between the ages of 60 and 84 who solicited U.S.-based independently operating sex providers online through sex provider review websites and discussion boards. The primary purpose of this study was to assess condom use and predictors of sexual risk taking among a population of older male clients of heterosexual prostitution.…”
Section: Objectives and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation